Enzymatic synthesis of RNA oligonucleotides. - Sharmeen, L (1987)
Using SP6 RNA polymerase and various synthetic DNA oligomers as templates (12-65 b), we have obtained efficient synthesis of RNA transcripts without the need for either primer or promoter. Gel analysis of transcripts made from templates of known size demonstrated a predominant single species, together with some minor bands. For a given template the major band had the same 5'-nucleotide as predicted from the 3'-nucleotide of the template. This synthesis procedure makes it possible to efficiently and conveniently make labeled or unlabeled RNA from synthetic DNA oligonucleotides.